Biomass-derived ultrathin mesoporous graphitic carbon nanoflakes as stable electrode material for high-performance supercapacitors. (5th May 2019) - Sankar, S.; Ahmed, Abu Talha Aqueel; Inamdar, Akbar I.; Im, Hyunsik; Im, Young Bin; Lee, Youngmin; Kim, Deuk Young; Lee, Sejoon
Abstract: With the motivation of materializing a high-performance electrode material for the high-energy supercapacitor, ultrathin mesoporous graphitic‑carbon was synthesized from biomass green-tea wastes via the KOH activation process combined with either of the water or the hydrochloric acid treatment. The water-treated graphitic‑carbon showed an interconnected ultrathin-nanoflake structure with a high porosity, while the hydrochloric acid-treated graphitic carbon exhibited an aggregated structure of irregular nanoparticles. The supercapacitor with an electrode of water-treated graphitic‑carbon nanoflakes displayed an enhanced specific capacitance of 162 F/g at 0.5 A/g. Furthermore, the device revealed an excellent cycle stability after multiple cyclic charge-discharge operations ( i.e., 121% cyclic capacitance retention over 5000 cycles). These may open up a new avenue toward the recycling of biomass carbonaceous resources ( e.g., green tea wastes) for inexpensive high-performance electrochemical energy-storage devices such as high-energy supercapacitors. Graphical abstract: Unlabelled Image Highlights: Graphitic carbon was derived from green tea wastes via KOH activation in air. The hydrolysis treatment resulted in the formation of graphitic-carbon nanoflakes. Graphitic-carbon nanoflakes showed an interconnected structure with high porosity ( i.e., pore volume ~ 0.4713 cm 3 /g). Graphitic-carbon nanoflakes played an excellent role as a supercapacitor electrode ( i.e., specific capacitance ~ 162 F/g). The results render a prospective way to the recycling of biomass waste resources.